The Future of Work : Exploring the Impact of Remote and Hybrid Work Models on Employee Productivity and Well-Being - Candra Candra; Joko Sabtohadi (Brilliant International Journal Of Management And Tourism, 2025)
This study investigates the impact of remote and hybrid work models on employee productivity and well being, two critical dimensions of performance in the evolving landscape of digital work. Despite the increasing adoption of flexible work arrangements, research remains fragmented regarding their holistic effects. This study addresses that gap by examining how work life balance mediates and organizational support moderates the relationship between work models and employee outcomes. Employing an exploratory qualitative approach, data were collected through semi structured interviews with 15 participants from the education, technology, and finance sectors. Thematic analysis revealed five core themes: work flexibility, work life balance, organizational support, mental well being, and motivation. Findings indicate that while flexibility enhances autonomy and efficiency, it can blur personal professional boundaries without adequate organizational support. Work life balance emerged as a critical mediator in sustaining productivity and psychological health, whereas organizational support moderated the effects of flexibility and stress. These results validate the theoretical framework based on the Job Demands Resources and Conservation of Resources models. The study concludes that remote and hybrid work models can improve performance and well being when supported by clear boundaries and inclusive organizational strategies. This research contributes a conceptual model for designing sustainable digital work environments and offers practical implications for human resource management in flexible settings.